Internet governance: Gambling on the periphery - Ewan Sutherland (International Telecommunications Society (ITS), 2014)
Use of the Internet by entrepreneurs has transformed gambling. Many have notionally located their businesses away from jurisdictions with heavy taxes and intrusive regulation, to offshore centres with very low taxes and regulations intended to prove their statistics and the avoidance of money laundering. Alderney and Gibraltar have been able to generate substantial revenues by offering such terms. Antigua and Barbuda had to engage in a WTO trade dispute with the USA, which it won, but has yet to be compensated. Larger countries responded slowly, by lightening their regulations and taxes. The flows of money have attracted criminals, some of whom bribe players for spot bets or even to fix matches. Despite the centrality of the Internet to these changes, the issue of gambling has remained peripheral to Internet governance, when it could learn and when it could contribute to finding solutions.
Keywords: 330; Internet; governance; gambling; gaming; law; enforcement